Polymerase chain reaction (PCR) primer design to identify SNP rs7901695 transcription factor 7 like 2 (TCF7L2) - Elsa Badriyya; Afifatul Achyar (UNIVERSITAS NEGERI PADANG, 2023)
ABSTRACT. Transcription Factor 7 Like 2 (TCF7L2) is a gene that produces a protein that controls the expression and function of several incretin hormones. One of the primary activities of incretin hormones is to increase insulin production, which is important in glucose and energy homeostasis. Single Nucleotide Polymorphism (SNP) in the TCF7L2 gene is reported to be association with Type II Diabetes Mellitus (T2DM). T2DM is featured by persistent hyperglycemia because of the decrease in insulin production, insulin resistance, or both. In patients with diabetes mellitus, chronic hyperglycemia can damage organ systems and cause metabolic abnormalities. SNP rs7901695 TCF7L2 gene has been linked to T2DM in a number of places, including South Asia, Iceland, and the United States. The polymorphism at location 112.994.329 from nucleotide Timine (T) to Cytosine (C) enables the recognition of SNP rs7901695. Polymerase Chain Reaction (PCR) was used to identify the polymorphism. The objective of this research was to generate a precise primer for the PCR recognition of the SNP rs7901695 in the TCF7L2 gene. The research's methodology comprises DNA isolation, primer designing with Geneious, target amplification with PCR, and DNA sequencing for bioinformatic analysis. As a result of the study, four primers for the SNP rs7901695 TCF7L2 gene have been developed. The reaction obtained two fragments, sized 177 and 367 bp. The primers used were rs7901695-F, rs7901695-R, rs7901695-F(C), and rs7901695-R(T), which were used to detect the T allele. ABSTRAK. Transcription Factor 7 Like 2 (TCF7L2) adalah gen yang menghasilkan protein yang mengontrol ekspresi dan fungsi beberapa hormon inkretin. Salah satu aktivitas utama hormon inkretin adalah meningkatkan produksi insulin, yang penting dalam homeostasis glukosa dan energi. Single Nucleotide Polymorphism (SNP) pada TCF7L2 gene dilaporkan adanya hubungan dengan Diabetes Mellitus Tipe II (DMT2). DMT2 ditandai dengan hiperglikemia persisten karena penurunan produksi insulin, resistensi insulin, atau keduanya. Pada penderita diabetes melitus, hiperglikemia kronis dapat merusak sistem organ dan kelainan metabolisme. Gen SNP rs7901695 TCF7L2 dilaporkan memiliki asosiasi dengan DMT2 di sejumlah daerah, termasuk Asia Selatan, Islandia, dan Amerika Serikat. SNP rs7901695 ditandai dengan polimorfisme pada lokasi 112.994.329 dari nukleotida Timin (T) menjadi Sitosin (C). Metode yang digunakan untuk mengidentifikasi polimorfisme adalah Polymerase Chain Reaction (PCR). Penelitian ini bertujuan untuk menghasilkan primer yang tepat untuk pengenalan PCR terhadap SNP rs7901695 pada gen TCF7L2. Metodologi penelitian meliputi isolasi DNA, perancangan primer dengan aplikasi Geneious, amplifikasi target dengan PCR, dan sekuensing DNA untuk analisis bioinformatik. Sebagai hasil penelitian, empat primer untuk deteksi gen SNP rs7901695 TCF7L2 telah dikembangkan. Dua fragmen, berukuran 177 dan 367 bp, diperoleh dari reaksi tersebut. Primer yang digunakan adalah rs7901695-F, rs7901695-R, rs7901695-F(C), dan rs7901695-R(T), yang digunakan untuk mendeteksi alel T.